Assessment of nutritional status of school going adolescent girls in a rural block of Haryana, India - ., Diksha; Saluja, Neelu; Choudhary, Seema; Pandey, S. M.; Kundu, Manish; Singh, Manisha (International Journal Of Community Medicine And Public Health, 2020)
Background: Good nutrition during adolescence is critical to cover the deficits suffered during childhood and should include nutrients required to meet the demands of physical and cognitive growth and development, provide adequate stores of energy for illnesses and pregnancy and prevent adult onset of nutrition-related diseases. Poorly nourished adolescent mothers are more likely to give birth to low birth weight babies, perpetuating a cycle of health problems which pass from one generation to the next. Therefore, this study was aimed to assess the nutritional status of school going adolescent girls of Agroha block of Haryana. Methods: Study area was two senior secondary and two high schools (randomly selected) of Agroha block of district Hisar (Haryana). Study design was school based cross-sectional study. Study participants were three hundred and forty-four adolescent girls studying in class 9th, 10th, 11th and 12th. Study tool was pre-designed and pre-tested questionnaire. Percentages and Chi- Square. Statistical Package for Social Sciences (SPSS) software version 20.0 was used. Results: Out of total girls, 8.72% were found to be thin followed by severely thin (0.58%). Thirteen (3.78%) girls were found to be overweight followed by obese (0.58%). Conclusions: Nutritional status of adolescent girls was found to be satisfactory.